L’enfance dans « La poétique de la rêverie ». Lire Bachelard avec Pontalis et la psychanalyse - Thiboutot, Christian (BACHELARD STUDIES - ÉTUDES BACHELARDIENNES - STUDI BACHELARDIANI, 2022)
The present article aims to contrast, but above all to reconcile, the conceptions of childhood as they unfold in Bachelard’s poetics, on the one hand, and in Pontalis’ meditation on psychoanalysis, on the other. In this spirit, the paper seeks to argue that both authors consider childhood to be profuse and inexhaustible, constituing therefore a horizon and an experience always open beyond itself, rather than something past or behind.